CIVIL SOCIETY ORGANISATIONS (CSOS) ENGAGEMENT IN RURAL DEVELOPMENT THROUGH POVERTY REDUCTION IN ODUKPANI LOCAL GOVERNMENT AREA OF CROSS RIVER STATE, NIGERIA. - Associate Prof Festus Nkpoyen, Dr. Francis Abul Uyang , Dr. Beauty Usoroh Kenneth, Dr Odike E Levi., Dr Ekaette Udoh, Utulu , Paul Benedict; Associate Prof Festus Nkpoyen, Dr. Francis Abul Uyang , Dr. Beauty Usoroh Kenneth, Dr Odike E Levi., Dr Ekaette Udoh, Utulu , Paul Benedict (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Civil Society Organization engagement in rural development is seen as a strategy for reducing poverty through the major domain of advocacy. It provides solution to social, political and economic dilemmas in rural communities where governmental presence is less significantly felt. Civil Society Organizations are supporters/facilitators of rural poverty reduction through providing rural dwellers relevant training and skills to broaden possibilities of self-production, social advocacy for participation in rural cooperative organization and engagement in rural health care delivery services especially during immunization. Both qualitative and quantitative approaches of survey research design were adopted to obtain data from 600 subjects in Odukpani Local Government Area in Cross River State, Nigeria. Findings indicated that Civil Society Organizations have played an active role in rural development to achieve a better/more affluent rural community. Through advocacy and policy reforms, CSOs can help address the deteriorating rural infrastructure and establish safety nets for vulnerable rural dwellers.